Academic Dependency - Fernanda Beigel (Alternautas, 2015)
As a research field, academic dependency is nourished on the social studies of science, critical epistemology and comparative studies of higher education. It encompasses the unequal structure of production and circulation of knowledge that has emerged historically along with the international scientific system. This structure is composed of institutional, material and symbolic processes, mutually related, which have produced different paths of academia-building. In the periphery, these combinations are the historical result of national and regional responses to internationalization – particularly given the diverse roles played by the state in scientific development and higher education.